Zentralbibliothek Zürich: A new library - ten years after - Köstler, Hermann (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
On the sixth of February 1629, four young citizens of Zurich founded a library that was open to the public: the Stadtbibliothek, or 'city library'. Because the library grew so quickly, the city council relocated it to the Wasserkirche, a church dating from the late Middle Ages that had been deconsecrated after the Reformation, and which is situated on an island in the river Limmat. From 1634 to 1917, that library served the dual goals of education and scholarship.